2001
DOI: 10.1152/ajpcell.2001.281.4.c1403
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonicity induces L-selectin shedding in human neutrophils

Abstract: Expression levels of adhesion molecules on neutrophils are affected under various conditions, including ischemia, possibly because of associated increases in cell volume. We examined the effects of cell swelling in hypotonic media on the level of L-selectin (CD62L) and beta(2)-integrin (CD18) on human neutrophils. In hypotonic media, neutrophils shed L-selectin. The shedding was greatly reduced by 30 microM RO31-9790, the metalloprotease (sheddase) inhibitor. Hypotonicity-induced L-selectin shedding was also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…We found that the fraction of neutrophils without L-selectin was significantly increased after rolling on the sLe x surface at 4 dyn/cm 2 . Leukocyte stimulation induced by chemotactic factors (15,17) or cell swelling in hypotonic media (19) gives rise to surface L-selectin cleavage, activating TACE. In addition, the crosslinking of L-selectin (16,22,34) also induces L-selectin downregulation from the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the fraction of neutrophils without L-selectin was significantly increased after rolling on the sLe x surface at 4 dyn/cm 2 . Leukocyte stimulation induced by chemotactic factors (15,17) or cell swelling in hypotonic media (19) gives rise to surface L-selectin cleavage, activating TACE. In addition, the crosslinking of L-selectin (16,22,34) also induces L-selectin downregulation from the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PMA, LPS, FMLP, and other chemoattractants can induce the down-regulation of L-selectin from the cell surface (13,15,17). It is also known that cell shrinking and swelling induced by hyper-or hypotonic media induce L-selectin shedding (18,19). TNF-␣-converting enzyme (TACE; ADAM-17) has been identified as a protease responsible for the cleavage of the extracellular domain of L-selectin by cellular activation (20,21).…”
mentioning
confidence: 99%
“…Others, such as synthetic sulfonated glycoproteins containing multivalent ligands presumably operate via the same mechanism as the crosslinking antibodies [23]. In addition, there are a number of other agents which induce L-selectin shedding, including LPS, both hypertonic and hypotonic shock, and chemotactic factors [2,24,25]. There are others that induce shedding of L-selectin without general cell activation which provide important information about this process.…”
Section: Agents Inducing L-selectin Sheddingmentioning
confidence: 99%
“…Crosslinking L-selectin by multivalent ligand or phenylarsine or varying osmotic pressure induces L-selectin shedding [12][13][14][15] , which can be inhibited by a hydroxamic acid-based peptide inhibitor of matrix metalloprotease KD-IX-73-4 (or TAPI-0) or [16,17] . One of the functionalities of L-selecting shedding is to regulate ARTICLES BIOPHYSICS leukocyte rolling over and binding to its ligand [18][19][20][21][22] .…”
mentioning
confidence: 99%